Analysis and Specifications for Appointment System Requirements at Pratama Clinics (Case study at the Indonesian Ministry of Religion Affairs) - Adita, Ita; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2025)
This research discusses the development of a web-based Appointment System (SIJAMU) for the Primary Clinic of the Indonesian Ministry of Religion. Prior to this system, clinics dealt with the problem of registering and scheduling appointments manually, resulting in inefficiencies, errors, and decreased patient satisfaction. SIJAMU is designed to automate this process, including reservations, schedule changes, managing patient and doctor data, and generating reports. This system adopts web-based technology to facilitate access and use by both patients and clinic admins. With SIJAMU, it is hoped that the registration and scheduling process can be carried out more efficiently, reduce errors and increase patient satisfaction. The results of system implementation show that SIJAMU can increase clinic operational productivity and provide better services, in accordance with the clinic’s needs and objectives in providing integrated and modern health services.